Pengujian Skala Pengukuran Kelelahan (Spk) pada Responden di Indonesia - Zuraida, Rida; Chie, Ho Hwi (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Subjective fatigue measurement instruments, based questionnaire, is a measure that is widely used for reasons of practicality and measurement results can be obtained quickly. For the purposes of measuring fatigue, there are a number of questionnaires commonly used abroad, but not a lot of literature with a case study in Indonesia that utilize this instrument. Of course, the reason for the use of the instrument is based on the expectation that the instrument has high validity and reliability, and if possible to have a high level of practicality as well. Asssment Fatigue Scale (FAS) is one of the suggested use as a measurement of worker fatigue. The instrument consists of a 10 item questionnaire with good reliability level. The discussion in this paper covers Measurement Scale Fatigue testing results via questionnaires measuring fatigue, adapted from the FAS in English and translated into Indonesian. DSS consists of 10 questions using 5 Likert scale, for the answer options are: never (1), sometimes (2), perceived a regular basis (3), is common (4), is always experienced (5). Relaibilitas test results using Cronbach alpha values obtained value of 0812, and can be improved if the item is question number 3 is removed. By implication, this questionnaire is good enough to use as a measuring instrument fatigue, but the level of proficiency in Indonesian language, in this CMS, needs to be repaired, especially for question number 5 and 3 if the level of validity and reliability to be improved, although the increase may not be too significant.